Research Progress in Establishment and Evaluation of Common Asthma Animal Models - LUO Shixiong; ZHANG Sai; CHEN Hui (Shiyan dongwu yu bijiao yixue)
Bronchial asthma (hereinafter referred to as asthma) is a common chronic respiratory disease characterized by airway inflammation, airway hyperresponsiveness, and airway remodeling. Its pathogenesis is highly complex and heterogeneous, involving multiple factors such as genetics, immunity, and environmental exposure. Currently, therapeutic options for asthma remain relatively limited, making it an urgent priority to explore its underlying mechanisms, identify effective treatment strategies, and develop new drugs. In this context, the establishment of animal models for asthma plays an irreplaceable and crucial role. However, to date, no single ideal animal model has been able to fully and accurately replicate all the features of the onset and progression of human asthma. This study systematically reviews the research progress over the past five years in the establishment methods of asthma animal models. It provides a detailed overview of commonly used experimental animals (such as mice, rats, and guinea pigs), frequently used sensitizing agents (including ovalbumin, house dust mite, lipopolysaccharide, and toluene diisocyanate), and the methods for establishing asthma models using these animals and sensitizers. This study also presents an objective evaluation of the advantages, limitations, and applicability of each model. Evaluation criteria for asthma models are summarized across multiple dimensions, including behavioral assessments, pulmonary function, histopathology, immunological indicators, and pharmacodynamics. Although methods for establishing refractory asthma models remain underdeveloped, several strategies for modeling refractory asthma have been summarized through a review of relevant literature, aiming to provide useful references for related research. Based on current scientific and technological advancements, it is anticipated that future research on asthma animal models will focus more on clinical relevance, technological innovation, and multidisciplinary integration. Specifically, future models are expected to adopt multi-sensitizer induction protocols, apply cutting-edge tools such as gene editing, enhance clinical relevance and promote diversification and personalization of models. Furthermore, advanced technologies such as bioimaging and biosensing are anticipated to enable dynamic monitoring of airway inflammation and remodeling. Organ-on-a-chip platforms may also be explored as potential alternatives to traditional animal models. The ultimate goal is to develop multifactorial, composite models that better simulate the complexity and heterogeneity of human asthma.